Sounds of the New Deal : the Federal Music Project in the West - Gough, Peter, 1960- (Music in American life., 2015)
At its peak the Federal Music Project (FMP) employed nearly 16,000 people who reached millions of Americans through performances, composing, teaching, and folksong collection and transcription. In 'Sounds of the New Deal', Peter Gough explores how the FMP's activities in the West shaped a new national appreciation for the diversity of American musical expression.